Analisis Financial Distress Menggunakan Metode Altman Z-Score, Springate, Zmijeski Dan Grover Pada Perusahaan Sektor Perkebunan yang Terdaftar di Bursa Efek Indonesia - Sri Fitri Wahyuni; Rubiyah Rubiyah (Magister Manajemen Universitas Muhammadiyah Sumatera Utara, 2021)
The purpose of this study was to analyze the financial distress conditions in plantation sector companies listed on the Indonesia Stock Exchange in 2014-2018 using the Altman Z-Score, Springate, Zmijewski and Grover methods. And to find out the level of accuracy of each method and the error rate of the Altman Z-Score, Springate, Zmijewski and Grover methods.This study uses a descriptive approach, which aims to determine the value of an existing variable. The data analysis method used is the Altman Z-Score, Springate, Zmijewski and Grover methods. The results of this study indicate that there are differences in results between the Altman Z-Score method, the Springate method, the Zmijewski method and the Grover method in analyzing the company's financial distress. The Altman method is the most appropriate and accurate method in predicting financial distress conditions in plantation sector companies listed on the Indonesia Stock Exchange with the highest accuracy rate of 76.00%, then the second is the Zmijewski method with an accuracy rate of 70.67% and the last Springate and Grover methods with the same level of accuracy that is equal to 69.33%